2018
DOI: 10.1002/anie.201804648
|View full text |Cite
|
Sign up to set email alerts
|

Rational Synthesis of Antiaromatic 5,15‐Dioxaporphyrin and Oxidation into β,β‐Linked Dimers

Abstract: 5,15-Dioxaporphyrin was synthesized for the first time by a nucleophilic aromatic substitution reaction of a nickel bis(α,α'-dibromodipyrrin) complex with benzaldoxime, followed by an intramolecular annulation of the α-hydroxy-substituted intermediate. This unprecedented molecule is a 20π-electron antiaromatic system, in terms of Hückel's rule of aromaticity, because lone pair electrons of oxygen atoms are incorporated into the 18π-electron conjugated system of the porphyrin. A theoretical analysis based on th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
25
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 43 publications
(25 citation statements)
references
References 86 publications
0
25
0
Order By: Relevance
“…The spectrum exhibitedasharp singlet signal for the b protons at d = 4.99 ppm (Figure 3c), which were, compared to 1,c onsiderably upfield shifted. Comparison of the chemical shifts of selected isophlorins with antiaromatic [7-14, 17, 18] and nonaromatic [3][4][5][6] characters, other relevant antiaromatic porphyrinoids, [29][30][31] and quinoidal thiophene compounds [32,33] is summarized in Ta ble S16. The peak of [2] 2À is shifted downfield compared to those of the stronga ntiaromatic analogues (from 3toÀ1ppm), but shifted upfield compared to those of the distortedn onaromatica nalogues and quinoidal thiophene compounds (from 8t o6ppm).…”
Section: Resultsmentioning
confidence: 99%
“…The spectrum exhibitedasharp singlet signal for the b protons at d = 4.99 ppm (Figure 3c), which were, compared to 1,c onsiderably upfield shifted. Comparison of the chemical shifts of selected isophlorins with antiaromatic [7-14, 17, 18] and nonaromatic [3][4][5][6] characters, other relevant antiaromatic porphyrinoids, [29][30][31] and quinoidal thiophene compounds [32,33] is summarized in Ta ble S16. The peak of [2] 2À is shifted downfield compared to those of the stronga ntiaromatic analogues (from 3toÀ1ppm), but shifted upfield compared to those of the distortedn onaromatica nalogues and quinoidal thiophene compounds (from 8t o6ppm).…”
Section: Resultsmentioning
confidence: 99%
“…In the UV/Vis/NIR absorption spectrum, 2 displayed three characteristic bands at 477, 434, and 329 nm and broad, ill-defined absorption ranging from 600 to 900 nm (Figure 3). This absorption profile,w hich is characteristic for antiaromatic conjugated systems, [11-23, 29, 30] can be explained on the basis of Michls4N-electron perimeter model [31] with the help of magnetic circular dichroism (MCD) spectroscopy.I n Michlst erminology,s ix frontier orbitals (hÀ, h + , sÀ, s + , lÀ, l +), which are derived from as ymmetry perturbation of the degenerate HOMO,s ingly occupied molecular orbital (SOMO) and LUMO of the 4N -electron perimeter model, [39] The thermal ellipsoids are scaled to the 50 % probability level. aand binthe top view denote the centers of sixmembered rings.…”
mentioning
confidence: 99%
“…Attempts to synthesize the target compound TriAAOP by sequential S N 2 reactions of 6 with several oxygen sources (Me 4 NOH, KOH, Ag 2 O) under various conditions were unsuccessful. However, we eventually found that the ring‐closure reaction of 6 with excess 4‐methoxybenzaldoxime/NaH, which had been used to synthesize DOP, afforded 20π TriAAOP 7 as a yellow solid. Treatment of 7 with silver(I) hexafluorophosphate in CH 2 Cl 2 instantaneously generated 19π radical cation 8 or 18π dication 9 depending on the content of oxidant used.…”
Section: Resultsmentioning
confidence: 93%
“…In addition to diazaporphyrin derivatives, 20π porphyrins modified with chalcogen atoms at the 5 and 15 positions have received considerable attention from both porphyrin and heteroatom chemists . Recently, Shimizu et al . and Shinokubo et al .…”
Section: Introductionmentioning
confidence: 99%